2010
DOI: 10.1128/aem.01688-09
|View full text |Cite
|
Sign up to set email alerts
|

Application of Molecular Techniques To Elucidate the Influence of Cellulosic Waste on the Bacterial Community Structure at a Simulated Low-Level-Radioactive-Waste Site

Abstract: Low-level-radioactive-waste (low-level-waste) sites, including those at various U.S. Department of Energy sites, frequently contain cellulosic waste in the form of paper towels, cardboard boxes, or wood contaminated with heavy metals and radionuclides such as chromium and uranium. To understand how the soil microbial community is influenced by the presence of cellulosic waste products, multiple soil samples were obtained from a nonradioactive model low-level-waste test pit at the Idaho National Laboratory. Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 62 publications
1
20
1
Order By: Relevance
“…and Streptomyces spp. is not surprising in heavymetal contaminated soil and their occurrence in this polluted environment was confirmed by several authors (Joynt et al 2006;Schmidt et al 2009;Field et al 2010;El-Meleigy et al 2011;Karelová et al 2011;Lin et al 2011;Al-Kadeeb et al 2012). Similarly, the occurrence of the bacterial subclass Rubrobacteridae clones is not surprising as well, because 70% of the actinobacterial clones belonged to the genus Rubrobacter, a widespread taxa that has yet few cultured representatives in soils (Holmes et al 2000).…”
Section: Resultssupporting
confidence: 52%
“…and Streptomyces spp. is not surprising in heavymetal contaminated soil and their occurrence in this polluted environment was confirmed by several authors (Joynt et al 2006;Schmidt et al 2009;Field et al 2010;El-Meleigy et al 2011;Karelová et al 2011;Lin et al 2011;Al-Kadeeb et al 2012). Similarly, the occurrence of the bacterial subclass Rubrobacteridae clones is not surprising as well, because 70% of the actinobacterial clones belonged to the genus Rubrobacter, a widespread taxa that has yet few cultured representatives in soils (Holmes et al 2000).…”
Section: Resultssupporting
confidence: 52%
“…Moreover, Field et al . () observed that members of Actinobacteria containing known cellulose‐degrading bacteria increased in the fill‐waste interface layer, which suggested the potential capabilities of the Actinobacteria phylum to degrade cellulose. Additionally, our previous studies found that extracellular organic matter (EOM) from M .…”
Section: Resultsmentioning
confidence: 95%
“…Strains in group 1 belonged to Gram‐negative bacteria, which were well supported by the studies that Rpf also resuscitated and stimulated the growth of some Gram‐negative bacteria (Su et al ., ,b, ,b,c,d). In particular, ZS2R8 was closely related to uncultured bacterium clone FW2_72B () which was detected at low‐level waste site with cellulosic contaminants (Field et al ., ). Strains in group 2 were closely related to Bacillus sp., which were low G+C Gram‐positive bacteria.…”
Section: Resultsmentioning
confidence: 97%
“…The type strain of Sulfuricella denitrificans was isolated from a cold anoxic hypolimnion of a freshwater lake, and was characterized as a psychrotolerant sulfur oxidizer (Watanabe et al, 2012). Based on nucleotide sequences, its close relatives have been found in freshwater lake sediments (Nelson et al, 2007;Song et al, 2012;Watanabe et al, 2013), Thioploca samples from two freshwater lakes (Nemoto et al, 2011), drinking water distribution systems (Li et al, 2010;Sun et al, 2014a, b), the sediment of a drinking water reservoir (Cheng et al, 2014), soil (Field et al, 2010), a bioreactor (Wang et al, 2015), subglacial sediment (Boyd et al, 2014), wetland sediment (Liu et al, 2014), a limestone aquifer (Herrmann et al, 2015), groundwater (Hong et al, 2013), black shale (Li et al, 2014), a horizontal subsurface flow system constructed in wetlands (Zhong et al, 2015) and the freshwater layer of a meromictic lake (Kubo et al, 2014). Members of the genus Sulfuricella are likely to contribute to sulfur cycling in a wide range of freshwater ecosystems, but only two cultured strains of the genus Sulfuricella have, so far, been described (Watanabe et al, 2015b).…”
mentioning
confidence: 99%